Landscape Elements for a Florida-Friendly Yard - Gail Hansen (EDIS)
ENH1163, a 5-page illustrated fact sheet by Gail Hansen, lists common elements of well-designed Florida yards, grouped into three categories: environmental health, function, and design. Includes references. Published by the UF Department of Environmental Horticulture, March 2010.